Antibodies in the Pathogenesis of Hypertension. (22nd June 2014) - Chan, Christopher T.; Lieu, Maggie; Toh, Ban-Hock; Kyaw, Tin S.; Bobik, Alexander; Sobey, Christopher G.; Drummond, Grant R.
Abstract : It has long been known that circulating levels of IgG and IgM antibodies are elevated in patients with essential and pregnancy-related hypertension. Recent studies indicate these antibodies target, and in many cases activate, G-protein coupled receptors and ion channels. Prominent among these protein targets are AT1 receptors, α 1 -adrenoceptors, β 1 -adrenoceptors, and L-type voltage operated Ca 2+ channels, all of which are known to play key roles in the regulation of blood pressure through modulation of vascular tone, cardiac output, and/or Na + /water reabsorption in the kidneys. This suggests that elevated antibody production may be a causal mechanism in at least some cases of hypertension. In this brief review, we will further describe the protein targets of the antibodies that are elevated in individuals with essential and pregnancy-related hypertension and the likely pathophysiological consequences of antibody binding to these targets. We will speculate on the potential mechanisms that underlie elevated antibody levels in hypertensive individuals and, finally, we will outline the therapeutic opportunities that could arise with a better understanding of how and why antibodies are produced in hypertension.